KORELASI JUMLAH MONOSIT DENGAN KADAR C-REACTIVE PROTEIN PADA PENDERITA TUBERKULOSIS - Ari Nuswantoro; Fitri Mega Astuti; Fitri Ulya Hartati; Aditia Aditia (Poltekkes Kemenkes Bandung, 2022)
Tuberculosis (TB) caused by Mycobacterium tuberculosis (MTB) is still a public health problem throughout the world, including in Indonesia. Monocytes play a role in cellular reactions against MTB bacteria and are considered a marker of active TB spread. C-Reactive Protein (CRP) examination is very useful for diagnosing inflammation or infectious diseases. This study aimed to determine the correlation between monocyte counts and CRP levels in TB patients in North Putussibau. This research was observational analytic with cross-sectional approach and the sampling technique was accidental nonprobability sampling. The sample was TB patients in North Putussibau who were undergoing treatment for 0, 2, and 6 months in 2022, resulting in 36 patients. Monocyte counts were examined using the fluorescence method and CRP levels were examined using the latex agglutination method. At 0 months of treatment, the monocyte count was obtained with an average of 1.096.88cells/µL and average CRP level of 55.13mg/L, at 2 months of treatment the average monocyte count was 742.31 cells/µL and CRP levels were obtained an average of 10.62mg/L, and after 6 months of treatment an average monocyte count was 414.29cells/µL and an average CRP level of 0mg/L. The Kendall's Tau-b test showed a significant value 0.000 (<0.05), which means there was a significant correlation between the number of monocytes and CRP levels in TB patients with a correlation coefficient 0.645 which shows the strength of strong relationship. This shows that the decrease in the number of monocytes and CRP levels is in line with the length of the TB treatment period.